The Potential of Silver Nanoparticles as Antibacterial and Antibiofilm Agents in Bacteria that Cause Periodontal Disease — A Literature Review - Fania Alfadin Uba; Komariah Komariah; Ciptadhi Tri Oka Binartha (CV. Publikasi Indonesia, 2026)
Background: Periodontal disease is a chronic inflammatory disease that is closely related to the activity of biofilm-forming pathogenic bacteria, such as Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola. Conventional therapies using antibiotics often face limitations in the form of bacterial resistance and side effects. Silver nanoparticles (AgNPs) are reported to have effective antibacterial and antibiofilm activity against a wide range of pathogenic microorganisms. Objective: This literature review aims to examine the potential of silver nanoparticles as antibacterial agents and antibiotics against bacteria that cause periodontal disease. Methods: Literature search was conducted through PubMed, Scopus, and Google Scholar scientific databases with relevant keywords. Results: The results of the study showed that AgNPs are able to inhibit the growth of periodontal bacteria through cell membrane damage, increased membrane permeability, disruption of intracellular metabolic processes, and inhibition of biofilm formation and maturation. Based on these findings, silver nanoparticles have the potential to be developed as an alternative or adjuvant therapy in the control of periodontal infections. Conclusion: However, further research is needed regarding safety and its clinical application.